ANALISIS BRAND EQUITY SEBAGAI ALAT BANTU PERENCANAAN STRATEGI PEMASARAN PADA KENDARAAN RODA EMPAT MEREK TOYOTA AVANZA - Hamdani, Saepul Rohman; Sudarijati, Sudarijati (Fakultas Ekonomi Universitas Djuanda, 2015)
In general, every company wants to achieve success in business, in the sense of always trying to get their business survival remain successful and running smoothly. National automotive industry in the modern era is experiencing significant growth, this affects the increasing number of manufacturers of four-wheeled vehicles are vying to grab a large market share. The aim of this study was to investigate and analyze brand equity as a planning tool in the marketing strategy of the brand Toyota Avanza four-wheel vehicles in the city of Bogor. In this study, analysis tools used are: Spearman-Brown validity test, reliability test, Cochrans test and Likert scale. The purpose of this study was to determine the response of consumers in the city of Bogor to the four-wheeled vehicle brand Toyota Avanza by measuring the level of brand awareness, brand association, perceived quality and brand loyalty. Based on the results of the questionnaire study of 100 respondents. These results indicate that the four-wheel drive brand awareness types of low Mpv four-wheel vehicles as the Avanza brand top of mind. Analysis of brand association brand Avanza currently has nine attributes forming the brand image. Results of analysis of quality brand Toyota Avanza perceived as a whole shows that the quality of performance (the consumers perception of the quality of the product) which is lower than the quality importance (of respondents to the expectations of the product). Brand loyalty for four-wheeled vehicles may be said Avanza brand loyal to the level like the brand.Keywords: Brand Awareness, Brand Association, Consumer Perception and Brand Loyalty